Character Education from an Islamic Perspective as a Foundation for Ethical and Responsible Citizenship - Muhammad Jailani (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2026)
Background : In the contemporary global context, rapid social change driven by globalization and technological advancement has generated ethical challenges such as moral degradation and declining civic responsibility. Objective : Therefore, this study examines character education from an Islamic perspective as a foundation for fostering ethical and responsible citizenship. Method : Using a qualitative library research approach, the study analyzes and synthesizes scholarly literature published between 2020 and 2025 from peer-reviewed journals indexed in SINTA and Scopus, with a focus on key concepts of Islamic character education, particularly the integration of faith (iman), knowledge (‘ilm), and righteous action (‘amal salih), and their implications for moral development and civic behavior. Findings and Implications : The findings indicate that Islamic character education offers a comprehensive value-based framework that integrates spiritual, moral, and social dimensions of education, contributing to the formation of individuals with strong moral awareness, ethical conduct, and social responsibility.Theoretically, this study contributes to the discourse on character and citizenship education by articulating an Islamic normative framework that complements and enriches predominantly secular models of ethical citizenship. Practically, it provides insights for the development of educational curricula and civic education programs that promote moral integrity, social cohesion, and responsible civic engagement in pluralistic societies. Conclusion : The study concludes that Islamic character education constitutes a relevant and viable foundation for developing ethical and responsible citizenship in both national and global contexts.